“I didn’t even wonder why I was on the floor” - mixed methods exploration of stroke awareness and help-seeking behaviour at stroke symptom onset - Busetto, Loraine; Stang, Christina; Herzog, Franziska; Sert, Melek; Hoffmann, Johanna; Purrucker, Jan; Seker, Fatih; Bendszus, Martin; Wick, Wolfgang; Ungerer, Matthias; Gumbinger, Christoph (BMC health services research, 2024)
To better target stroke awareness efforts (pre and post first stroke) and thereby decrease the time window for help-seeking, this study aims to assess quantitatively whether stroke awareness is associated with appropriate help-seeking at symptom onset, and to investigate qualitatively why this may (not) be the case.